Criminal minds. the fifteenth season [videorecording (DVD)]. - Mantegna, Joe; Gubler, Matthew Gray, 1980-; Cook, A. J., 1978- (Paramount, 2020)
Criminal minds revolves around an elite team of FBI profilers who analyze the country's most twisted criminal minds, anticipating their next moves before they strike again.